RESULTS OF THE TECTONOPHYSICAL STUDY IN THE DZHANKHOT THRUST ZONE (NORTHWESTERN CAUCASUS) - A. V. Marinin; T. Yu. Tveritinova (Геодинамика и тектонофизика)
The paper presents the results of detailed structural analysis of the Dzhankhot thrust zone which is a part of the system of overthrust nappe structures in the southern slope of the Northwestern Caucasus. The relevance of the research topic is found on the reason that despite the obvious importance of these overthrust nappes in the structure of the Greater Caucasus there is still lack of in-situ observational data on the detailed structure of thrust zones and on tectonic stress distribution pattern therein.As a result of the structural and geological studies of small disjunctive and plicative forms in the Upper Cretaceous and Paleocene sediment contact along the Dzhankhot thrust, there were identified the major structural and tectonic deformation patterns and the areal distribution of tectonic deformations depending on the distance to the thrust. There was determined the major type of stress in different parts of the thrust zone. There was shown the difference in the development of geological indicators of faults for different elements of the folded structures. In some cases, there was determined the sequence of deformations, from synsedimentary structures (clastic dikes in particular) to post-sedimentary brittle structures.The orientation of principal stress axes determined from the reconstruction data by method of cataclastic analysis of faults confirms a thrust-type deformation within the studied area near the Dzhankhot thrust. Local stress-tensor determinations are in good agreement with the location of observation points in the regional tectonic structure. Trajectories of the maximum compression axes, most of which are submeridionally and NNW-trending, change orientation to the northwest in the immediate vicinity of the Dzhankhot thrust fault zone. The identified features of tectonic structure and stressed-strained state of the Dzhankhot thrust zone allow considering this area as a natural structural and tectonophysical testing ground for both tectonic-stress-reconstruction-improvement methodologies and a study on natural deformation structures of the Greater Caucasus.